Impact of nine years of conservation tillage and precise nutrient management on equivalent yields, soil microbial dynamics, and water-energy footprints of the maize–mustard rotation - Lakhena, K. K.; Pooniya, Vijay; Biswakarma, Niraj; Zhiipao, R. R.; Singh, Arjun; Kumar, Dinesh; Shivay, Y. S.; Govindasamy, P.; Bana, R. S.; Rathore, S. S.; Upadhayay, P. K.; Barman, Anamika; et al. (Frontiers in Sustainable Food Systems, 2025)
In South Asian regions, the traditional maize–mustard rotation (MMR) has become less profitable and unsustainable due to inappropriate fertilization practices and the degradation of soil properties. Therefore, climate-smart and sustainable farm practices are necessary to mitigate production risks and improve soil properties. This study evaluated the long-term impacts of conservation tillage and nutrient management on equivalent yields, soil microbial properties, and water-energy savings. A long-term field experiment was initiated 9 years ago, using the split-plot design to evaluate the three conservation tillage (CA)-based crop establishment practices, i.e., zero tillage (ZT) and conventional tillage (CT), permanent beds (PNB). Each practice was accompanied by the recommended dose of fertilizer (RDF), improved RDF (RDFI), and nutrient expert-guided (NEI) fertilization. CA-based tillage (ZT or PNB) resulted in 24.4–25.2% greater maize grain equivalent yields (EY) compared to the CT, while the NEI and RDFI produced statistically (p = 0.05) identical EY, being 26.6–30.3% greater than the RDF. These practices substantially reduced the water footprints, besides 11.9–12.9% and 23.4–26.6% (9-yrs average) greater water productivity compared to CT and RDF, respectively. In fact, at 0–45 cm soil depth, residues retained ZT or PNB had 31.9–42.2%, 56.5–67.2%, and 16.5–18.3% more bacterial (107), fungi (104), and actinomycetes (104) populations, respectively. Across soil depths, ZT or PNB recorded 7.65–11% and 23.2–31.9% greater soil microbial biomass-C and -P, respectively. Compared to CT-based practices, these practices also improved soil mineralizable N (NO3− N/NH4+ N). The conventionally tilled plots consumed greater direct and indirect non-renewable energy than the CA-based residue-retaining practices. By virtue of residue retention, the PNB and ZT had 108% greater energy input (EI) than the CT, whereas it was vice versa in terms of the energy output (EO). The NEI registered a 7.6–28.7% higher EO than the RDFI and RDF. These long-term field studies demonstrated that adopting CA-based ZT, or PNB, in combination with precise nutrient management would enhance equivalent yields and soil microbial dynamics, besides improving water-energy footprints in maize–mustard growing ecologies.